Impact of forest management on genetic diversity of Quercus petraea populations: a case study from the Křivoklátsko Protected Landscape Area (Czech Republic) - Pospíšková, Markéta; Dostálek, Jiří (Biodiversity: Research and Conservation, 2010)
In the Křivoklátsko Protected Landscape Area (Czech Republic), the relation between genetic diversity and intensity of management was studied in 3 populations of Quercus petraea (Mattuschka) Liebl. (sessile oak). Microsatellite analysis was used to assess genetic diversity. The results indicate that differences between populations in average number of alleles per locus are so small that no genetic difference can be proved between them. The values of heterozygosity for all 3 studied populations confirm the absence of significant genetic differences among them.